A metric study of insole foot impressions in footwear of identical twins. (November 2017) - Nirenberg, Michael S.; Krishan, Kewal; Kanchan, Tanuj
Abstract: Foot impressions are of utmost importance in crime scene investigations. Foot impressions are available in the form of barefoot prints, sock-clad footprints, and as impressions within footwear. Sometimes suspects leave their footwear at the crime scene, and the insole of this footwear may contain the foot impression of the suspect which may be important evidence linking him or her to the crime. The task of identification based on the analysis of footprints can be challenging when the footprints belonging to one of the identical twin is available for examination. The present study is based on the quantitative measures of the foot impressions in the footwear of adult identical twins. The study was conducted on four sets of female monozygotic twins from the United States of America. A total of 17 length and breadth measurements were taken on each foot impression. A combination of Reel Method and Extended Gunn Method was utilized to produce the measurements. The measurements of the foot impressions were compared among the twins on the right and the left side. Differences were found in the various footprint measurements among the twins. The study's sample size was not large enough to apply robust statistical tests, but the study is significant in that it presents the first detailed comparative analysis of a large number of measurements of insole foot impressions of adult twins. The observations derived from the study are likely to assist forensic investigations in cases involving the foot impressions of the twins. Highlights: Analysis of quantitative measures of foot impressions in the footwear of identical twins. A total of 17 length and breadth measurements were taken of each foot impression. A combination of the Reel Method and Extended Gunn Method was utilized. Study observations are likely to aid in forensic investigation of cases involving foot impressions of the twins.